Epoetin beta pegol alleviates oxidative stress and exacerbation of renal damage from iron deposition, thereby delaying CKD progression in progressive glomerulonephritis rats. Issue 12 (3rd December 2015) - Hirata, Michinori; Tashiro, Yoshihito; Aizawa, Ken; Kawasaki, Ryohei; Shimonaka, Yasushi; Endo, Koichi
Abstract: The increased deposition of iron in the kidneys that occurs with glomerulopathy hinders the functional and structural recovery of the tubules and promotes progression of chronic kidney disease (CKD). Here, we evaluated whether epoetin beta pegol (continuous erythropoietin receptor activator: CERA), which has a long half‐life in blood and strongly suppresses hepcidin‐25, exerts renoprotection in a rat model of chronic progressive glomerulonephritis (cGN). cGN rats showed elevated urinary total protein excretion (uTP) and plasma urea nitrogen (UN) from day 14 after the induction of kidney disease (day 0) and finally declined into end‐stage kidney disease (ESKD), showing reduced creatinine clearance with glomerulosclerosis, tubular dilation, and tubulointerstitial fibrosis. A single dose of CERA given on day 1, but not on day 16, alleviated increasing uTP and UN, thereby delaying ESKD. In the initial disease phase, CERA significantly suppressed urinary 8‐OHdG and liver‐type fatty acid–binding protein (L‐FABP), a tubular damage marker. CERA also inhibited elevated plasma hepcidin‐25 levels and alleviated subsequent iron accumulation in kidneys in association with elevated urinary iron excretion and resulted in alleviation of growth of Ki67‐positive tubular and glomerular cells. In addition, at day 28 when the exacerbation of uTP occurs, a significant correlation was observed between iron deposition in the kidney and urinary L‐FABP. In our study, CERA mitigated increasing kidney damage, thereby delaying CKD progression in this glomerulonephritis rat model. Alleviation by CERA of the exacerbation of kidney damage could be attributable to mitigation of tubular damage that might occur with lowered iron deposition in tubules. Abstract : This study indicates that a single dose of epoetin beta pegol (CERA) mitigates exacerbation of kidney damage, thereby delaying CKD progression in a glomerulonephritis rat model. CERA treatment suppressed oxidative stress, which would be involved in help regeneration of tubular cells. In addition, the alleviation by CERA of the exacerbation of kidney damage could be attributable to mitigation of tubular damage as a result of lowered iron deposition in the tubules.